Factors affecting the Nd(3+) (REE(3+)) luminescence of minerals - Lenz, Christoph (Mineral Petrol, 2013)
In this paper, possibilities and limits of the application of REE(3+) luminescence (especially the Nd(3+) (4)F(3/2) → (4)I(9/2) emission) as structural probe are evaluated. Important factors controlling the Nd(3+) luminescence signal are discussed, including effects of the crystal-field, crystal orientation, structural state, and temperature. Particular attention was paid to the study of the accessory minerals zircon (ZrSiO(4)), xenotime–(Y) (YPO(4)), monazite–(Ce) (CePO(4)) and their synthetic analogues. Based on these examples we review in short that (1) REE(3+) luminescence can be used as non-destructive phase identification method, (2) the intensities of certain luminescence bands are strongly influenced by crystal orientation effects, and (3) increased widths of REE(3+)-related emission bands are a strong indicator for structural disorder. We discuss the potential of luminescence spectroscopy, complementary to Raman spectroscopy, for the quantitative estimation of chemical (and potentially also radiation-induced) disorder. For the latter, emissions of Nd(3+)-related centres are found to be promising candidates.